2006
DOI: 10.1590/s0004-28032006000300015
|View full text |Cite
|
Sign up to set email alerts
|

The cytoprotective effect of a nitric oxide donor drug on gastric mucous membrane of rats treated with ketoprofen, a non-steroidal anti-inflammatory drug

Abstract: -Background -Non-steroidal anti-infl ammatory drugs are considered today a very important group of medication, with a wide variety of therapeutic use, in different areas of modern medicine. Despite their benefi cial effects on the patient, these drugs show a high incidence of side effects, mainly in the gastrointestinal tract. The physiopathological mechanisms of non-steroidal anti-infl ammatory drugs induced lesions and the gastric mucosa defense mechanism became an important source for medical research, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Conflicting results are reported in the literature as to the role of NO in NSAIDs induced gastrotoxicity. While some studies suggest the clear ability to revert gastric mucous membrane alterations (Kato et al, ; Villa et al, ), other studies link NOSII expression and consequent NO overproduction to the development of gastrointestinal inflammatory disorders. A general interpretation of the above results is that physiological NO concentration, regulated by the NOSI enzymatic expression, is key in maintaining the gastric mucous membrane function, whereas NO overproduction by NOSII expression would result in a cytotoxic activity possibly mediated by oxygen free radicals (Calatayud et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results are reported in the literature as to the role of NO in NSAIDs induced gastrotoxicity. While some studies suggest the clear ability to revert gastric mucous membrane alterations (Kato et al, ; Villa et al, ), other studies link NOSII expression and consequent NO overproduction to the development of gastrointestinal inflammatory disorders. A general interpretation of the above results is that physiological NO concentration, regulated by the NOSI enzymatic expression, is key in maintaining the gastric mucous membrane function, whereas NO overproduction by NOSII expression would result in a cytotoxic activity possibly mediated by oxygen free radicals (Calatayud et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐inflammatory chemotherapeutics are commercially categorized into steroidal and nonsteroidal (nonsteroidal anti‐inflammatory drugs; NSAIDs) . The exact mechanism of action of NSAIDs is not known but it is probably related to the decrease in the fatty acid entering the cell or released from the cell .…”
Section: Introductionmentioning
confidence: 99%
“…The NO levels are slightly elevated in vardenafil pretreated rats in our study; however, the level of NO in either of vardenafil groups did not surpass the level of NO determined in the sham group. Some studies revealed gastroprotective effects of some agents without significant alterations in NO or MDA levels [31] . Determination of tissue cGMP level was not included in our study design.…”
Section: Karakaya K Et Al Gastroprotective Effects Of Vardenafilmentioning
confidence: 99%